Queen Ṭǝru Wärq’s Necklace - Pankhurst, Richard (Aethiopica, 2009)
Miscellaneous Article The article, which traces the Ethiopian history of beads and necklaces, focuses on an unpublished necklace which belonged to Emperor Tewodros’s consort Queen Ṭǝru Wärq. Acquired by Robert Napier, apparently after her death in 1868, it was presented by Napier to the then British Prime Minister Benjamin Disraeli. The necklace, though unique, is in Ethiopia’s necklace tradition; and utilizes the country’s three main traditional types of jewellery: silver caskets, silver filigree, and glass beads. A work of some sophistication it is not without artistic, as well as historical interest.